MITIGASI BENCANA ALIRAN DEBRIS SUNGAI BELANTING SECARA NON STRUKTURAL DESA BELANTING KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR – NUSA TENGGARA BARAT - Legiarto, Ahad; Legono, Djoko; Haryono, Haryono (Civil Engineering Forum Teknik Sipil, 2008)
Belanting village, situated in the foot of Rinjani mountain range and crossed over by Belanting River, is a fast-growing village. Almost all of its inhabitants are migrants who came there on their own support. On January 21, 2006, a disaster strucked: debris flow came, taking people’s lives and creating havoc to local infrastructures. One of the difficulties in the area is that the lack of non-structural disaster mitigation. At this rate, a study is required concerning the awareness of local inhabitants of the threat posed by debris flow hazard. The objective of the study is to identify the level of local people’s understanding on debris flow disaster, to be functioned as determining basis for disaster management pattern by non-structural mitigation. Data were collected from questionnaires and interviews for 80 respondents. The resulting questionnaire data were then analyzed using SPSS (Statistic Pocket for Social Science). Result of the analysis indicates that 52.5 per cent of respondents have not understood the threat of disaster. In the meantime, the interviews indicate that religious leaders (Tuan Guru) hold high social status. Based on the result of the analysis and interviews, there is a need for a strategy in non-structural mitigation program and, as far as the study is concerned, socialization during public religious learning regarded as more effective and efficient efforts.